Perbedaan Perhitungan Pajak Penghasilan Pasal 21 Dokter Sebagai Karyawan Tetap dan Dokter Sebagai Tenaga Ahli - Wira Afsari Wanandhita; Asaprima Putra Karunia; Trisninik Ratih Wulandari; Meka Sabilla Salim (Jurnal Akuntansi dan Pajak, 2023)
The purpose of this research is done to find out how the differences in the calculation of income tax 21 from doctors as permanent employees and doctors as experts. Another goal is to find out which is more profitable for doctors in determining employment status. This analysis was carried out by comparing the applicable regulations and practices carried out by PT.A. The quantitative data obtained were processed by descriptive analysis. The results of this analysis are differences in the tax basis, the components of income, and the use of non-taxable income as a deduction from gross income. The conclusion obtained for the sample of dr. DC is more profitable to use permanent employee status, dr. TY is more profitable with expert status, and dr. BB is more profitable with permanent employee status. Keywords : Income Tax 21, Doctor, Permanent Employee, Expert.